Problems and prospects of investment climate development in Ukraine - Vladyslav Krylovskyi (University Economic Bulletin, 2025)
Deepening institutional instability, increasing regulatory uncertainty, and growing infrastructure imbalances in the context of a full-scale war in Ukraine have created a threat to the sustainability of the investment environment, which has led to the need to rethink the factors of its formation and adapt to the conditions of postcrisis transformation. The purpose of the study was to identify the factors of the dynamics of the investment climate in Ukraine in 2020-2024, while simultaneously forming strategic guidelines for its improvement in the context of the post-war recovery. The methodological basis of the study was founded on an analytical and descriptive approach using elements of comparative, structural, functional, and institutional analysis. As a result of the study, five interrelated approaches to the interpretation of the investment climate - institutional, legal, economic, infrastructural and social - were identified, which allowed forming a five-level analytical model of the investment environment, presented in the format of a structural typology. Based on the analysis of the Rule of Law (-0.80 in 2022), Control of Corruption (-0.88 in 2022) and Corruption Perceptions Index (growth from 30 to 35 points in 2020-2024), it is determined that institutional quality is a key predictor of fluctuations in the volume of foreign direct investment (from 7.9 billion USD in 2021 to 0.2 billion USD in 2022). Critical barriers to creating a favourable investment climate are identified - regulatory instability, fiscal fragmentation, infrastructure degradation, and institutional vulnerability. Strategic directions for modernising the investment environment, including strengthening legal certainty, deregulation, restoring infrastructure and institutional support for investors, are substantiated. The proposed approaches were based on the successful practices of Poland, Estonia, Latvia, Georgia, and Romania, where structural reforms have ensured the growth of long-term investment in strategic sectors. The results obtained show the defining role of institutional quality as a critical factor of investment attractiveness in a transformational economy. The practical value of the study is to form an analytical basis for improving state investment policy aimed at increasing institutional capacity, reducing regulatory risks and stimulating long-term investment.
Keywords: 330; institutional capacity; regulatory environment; regulatory risks; macroeconomic stability; infrastructure support; transformational economy